2012
DOI: 10.5249/jivr.v4i2.122
|View full text |Cite
|
Sign up to set email alerts
|

Violence and self-reported health: does individual socioeconomic position matter?

Abstract: Abstract:Background:Violence is a major public health problem. Both clinical and population based studies shows that violence against men and women has physical and psychological health consequences. However, elsewhere and in Sweden little is known of the effect of individual socioeconomic position (SEP) on the relation between violence and health outcomes.Objective:This study aimed to assess the effect of individual SEP on the relation between violence and three health outcomes (general health, pain and anxie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 28 publications
2
16
1
2
Order By: Relevance
“…In line with some previous researches [7, 39, 40], we also found that older age, socio-economic disadvantages, and geographical location were positively associated with somatic symptoms in this sample. It is noteworthy that the country of residence was a risk factor for some countries (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…In line with some previous researches [7, 39, 40], we also found that older age, socio-economic disadvantages, and geographical location were positively associated with somatic symptoms in this sample. It is noteworthy that the country of residence was a risk factor for some countries (e.g.…”
Section: Discussionsupporting
confidence: 92%
“…However, we did not find significant association between the social group and SRH. In our study the professional qualification was not a determinant of SRH, although some publications present evidences about negative self-rated health of lower qualified and overqualified workers (13,18,23,28).…”
Section: Discussioncontrasting
confidence: 53%
“…But, it is not only upbringing that shapes the life course. There are a present environment being faced [82] , [99] , [111] , [112] , [115] , [116] , [117] and a past including an inheritance [76] , [118] , [119] . Different exposures in different time periods are intertwined in an accumulating fashion [28] , [83] , [85] , [99] , [112] , [120] or in certain critical periods [74] , [75] , [96] , [99] , [106] , [121] , [122] with potentially negative stress as outcomes [101] , [105] , [107] , [123] , [124] , [125] , [126] , [127] , [128] .…”
Section: Understanding the Complex Association Between Self-reported mentioning
confidence: 99%